Extracorporeal liver support techniques: a comparison - Riva, Ivano; Marino, Antonella; Valetti, Tino Martino; Marchesi, Gianmariano; Fabretti, Fabrizio (Journal of artificial organs, 2024)
ExtraCorporeal Liver Support (ECLS) systems were developed with the aim of supporting the liver in its detoxification function by clearing the blood from hepatic toxic molecules. We conducted a retrospective comparative analysis on patients presenting with liver failure who were treated with different extracorporeal techniques in our intensive care unit to evaluate and compare their detoxification abilities. To verify the effectiveness of the techniques, mass balance (MB) and adsorption per hour were calculated for total bilirubin (TB), direct bilirubin (DB), and bile acids (BA) from the concentrations measured. MB represents the total amount (mg or mcMol) of a molecule removed from a solution and is the only representative parameter to verify the purification effectiveness of one system as it is not affected by the continuous production of the molecules, released in the circulation from the tissues, as it is the case for the reduction rate (RR). The total adsorption per hour is calculated by the ratio between MB and the time duration and shows the adsorption ability in an hour. Our comparative study shows the superior adsorption capability of CytoSorb system regarding TB, DB, and BA, evaluated through the MB and adsorption per hour, in comparison with CPFA, MARS, Prometheus, and PAP. In conclusion, as extracorporeal purification in liver failure could be considered useful for therapeutic purposes, Cytosorb, being more performing than other systems considered, could represent the device of first choice.